ANALYSIS OF PORK RAW MATERIAL CONTROL MANAGEMENT USING THE ECONOMIC ORDER QUANTITY METHOD IN THE MARKET IN RUTENG CITY - M. A. A., KARLINA; TUKAN, H. D.; DALLE, N. S.; NUGRAHA, E. Y. (Majalah Ilmiah Peternakan, 2024)
This study aims to support the control of fresh pork raw materials in order to find out how much traders have implemented raw material inventory control and to find out the amount of continuity of raw material inventory. The research took place from January to March 2024 in the Ruteng city market, Manggarai Regency, NTT Province by interviewing 47 respondents. The analysis method used is a quantitative descriptive method to determine the optimal inventory of raw materials and continues with the analysis of the EOQ (Economic Order Quantity) method. The results of the study show that the total procurement cost by traders is IDR. 119,059,800/year and the total storage cost is IDR. 326,191.23/year and the average amount of IDR that traders have to pay to produce one Kg per day is IDR. 362,230.39/day. The results of the analysis regarding the control of raw material inventory by the EOQ method in traders can be concluded that: The average supply of fresh pork by traders increased in December at 3,014 Kg, the frequency of the quantity of each trader ordering fresh pork is 40 times a year and 573.5 Kg per year and 72.47 Kg per week and to overcome the stock of fresh pork is maintained, traders must immediately place an order when the inventory in the freezer has reached 145 Kg.